The Relationship Between Urban Green Spaces and Residents’ Mental Health: A Test of Physical Exercise’s Mediating Role - Ruifeng Tian (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study examines the relationship between urban green spaces and residents' mental health, specifically focusing on the role of physical exercise as a mediator. These findings have important implications for urban planning, public health policy, and individual health promotion. This study utilised a cross-sectional design and included 2647 participants from the 2021 China General Social Survey (CGSS 2021), with an average age of (51.34±17.57) years. The study employed the instruments from CGSS 2021 to examine participants' perception of urban green spaces, physical exercise status, and mental health. Data analysis was conducted using SPSS version 21.0 and Stata 12.0. The analysis included Spearman's and Pearson's correlation methods, as well as multi-variable linear regression and mediation analysis. The study revealed a strong positive correlation between urban green spaces, physical exercise engagement, and the promotion of mental well-being. However, there was no statistically significant relationship found between the amount of urban green spaces and the frequency of exercise. Furthermore, after controlling for other variables, a significant positive correlation was found between the presence of urban green spaces and the mental well-being of the community. This relationship was partially mediated by physical exercise. The findings offer a scientific foundation for future urban planning, green space construction, and public health policy formulation. They also provide valuable references for enhancing residents' quality of life and promoting mental health.